Motivation of Students of Faculty of Education (University of Seville) to physical activity practice - Campos Mesa, Mª del Carmen; Castañeda Vázquez, Carolina (FEADEF, 2012)
the aim of this research is to study students´ motivation for physical activity and sport in Faculty of Education of University of Seville. The sample (N=409) is constituted for students from this Faculty (±4.8%; 95%CI) and a specific questionnaire, built to that effect and structured in five sections, was used to obtain dates. This instrument was validated by different experts on this area of studies, statistic tests was done to check its reliability (Alpha Cronbach: .78) and factor analysis has been done in certain items, using SPSS V.15. The main results showed that the main motives to physical activity practice are related to be in good health and aesthetics, enjoyment and social relations, meanwhile, the main motives to have not ever practice physical activity or have given it up, are both related to time availability or lack of time, interest to physical activity and sport offer